Underutilised Resources in Urban Environments - Sigrid Kusch-Brandt (Resources, 2020)
An important opportunity for more sustainable development pathways in an urbanising world is missed where resources remain underutilised, when they could be valorised in a sound and environmentally favourable mode. This Special Issue of the journal Resources was initiated to identify promising solutions and specific challenges in the context of underutilised resources in urban environments. The compiled contributions address two main areas, namely the establishment of circular economy schemes based on valorising wastes that occur in urban areas and the exploitation of renewable energies. Circular economy and renewable resources hold key potential for making cities more sustainable, and the authors of this Special Issue, with their publications, enhance our understanding of how to unlock this potential. Effective regulatory frameworks and policymaking processes which balance the powers between stakeholders are required to successfully manage energy transition and the transition to more circular economies. The positive role of community engagement merits high attention. To recover valuable resources from household waste, a focus on technology and infrastructure is required but is not enough; motivational factors and knowledge of citizens are most essential elements. It also becomes evident that the need to more reliably quantify and better characterise recyclable material streams, especially where population numbers are further growing, remains. The publications compiled in this Special Issue are a rich source to identify promising solutions, challenges and research needed for the sound management of urban resource demands.